The electron g factor for one-band and two-band extended models of the electron energy spectrum - Mikitik, G.P.; Sharlai, Yu.V. (Физика низких температур, 2004)
At present, explicit expressions for the electron g factor in crystals are known only for the following
two cases: either the Fermi energy εF of the electrons lies at the edge of the electron energy
band, ε (kex), or the electron energy spectrum of a crystal can be approximated by the two-band
model. Here we obtain explicit formulas for the g factor in situations when the Fermi level ε F is
close to but does not coincide with the band edge and when the two-band model of the spectrum
includes small corrections from other electron energy bands. In particular, we derive the expressions
that describe the dependences of the g factor on ε F - ε (kex) and on the direction of the magnetic
field for doped semiconductors. The results are applied to III–V semiconductors and to bismuth.